A escrita e o emoji : uma reflexão semiológica pela interpretância da língua. - Costella, Roberta (2022)
The central element of this thesis lies in comprehending the emoji, from the perspective of the language, through a semiological reflection, the semiology of the Benvenistian language, with the objective of studying how it shows Benveniste's reflection on the nature of writing in his relationship with language interpretation. We propose two guiding questions. Question 1: What role does emoji have in the field of writing? Guiding question 2: Considering that Benveniste, in his last classes, formulates a hypothesis about the nature of writing in its relation with language, how do emojis contemplate what Benveniste says in this relation? From these questions, when dividing this paper into three chapters based mainly in the article Semiologia da língua (1969) and in the work Últimas aulas no Collège de France (1968-1969/2014), we built the hypothesis that the emoji is an element of the same nature as writing when we think about Benveniste's proposal in the Últimas aulas no Collège de France (1968-1969/2014), in which he describes the nature of writing through the interpretation of language. The emoji, an element belonging to writing, would be a possibility of representing the written language, the re-presentation, the secondary speech that Benveniste presents to us in the last classes. The research is qualitative and in terms of its objectives, it is exploratory and descriptive in nature. We believe, therefore, that the emoji is an element with a purpose similar to that of writing – responsible for the self-semiotization of the language – as it can be treated by the interpretation of that language. The one who interprets everything, including itself.